BLENDED LEARNING IN TEACHING MATHEMATICS - Helsa, Yullys; Darhim, Darhim; Juandi, Dadang; Turmudi, Turmudi (UNIVERSITAS MUHAMMADIYAH METRO, 2021)
The background of this research was the development of blended learning in teaching mathematics. This study aimed to determine the benefits of blended learning in teaching mathematics by analyzing previous research. The method in this study is a systematic literature review (SLR), it descriptive based survey in the form of an analysis of 25 articles from the Science Direct database in the 2010-2020 period. The results showed that there are many benefits of blended learning in mathematic, which includes: to improve mathematical thinking skills, develop good perceptions, improve learning outcomes, increase self-regulation, increase thinking/problem-solving skills, improve communication skills, increase student participation, simplify the assessment process, increase computational thinking skills, and critical thinking skills. The most significant benefit of blended learning is student learning outcomes, shown in 52% of the articles. The research implies the importance of supporting teachers in identifying the objectives of blended learning.